I Jornada de Historia de la Enfermería: Retrato de la Enfermería en el Ocaso del Siglo XVI - Manuel Ferreiro Ardións (Universidad de Alicante, 2017)
In this brief review, the author informs us about what happened in the course of the first day of History of Nursing in Álava, which focused on nursing in the late sixteenth century and especially in the presentation of the book: Herrera, a barber surgeon in the plague of 1599 in Vitoria.